Little steps, big counts: The literature review of parental play on early Math learning - Nur Arissa Khadijah Rozi; Nurul Syakira Mohd Shazwan Elmey; Juppri Bacotang; Noor Hanim Harun; Norfaizatulakma Johari; Andi Nur Nabilah Syafiqah Bacho; Nur Faradilla Jumati; Rashidin Idris (Quantum Academic, 2025)
This article examines the role of play-based learning in the development of early mathematics skills, drawing on data from current international research covering 2016 to 2024. Drawing on research from Asia, Europe, Africa, and Australia, the review finds major influences on early math learning, including the significance of interactive and nature-based play, instructor knowledge, parental beliefs, and home-school collaboration. A thematic analysis demonstrates that play-based tactics regularly improve children's mathematical engagement, motivation, and accomplishment. Educators show a high degree of understanding and support for such approaches, whereas parents generally have good beliefs but encounter practical limitations in fully participating. Despite the established benefits, structural challenges such as inadequate basic skills, misconceptions about mathematics, and fragmented implementation continue to impede development. The research finds that fostering solid early numeracy foundations requires a comprehensive, collaborative strategy that includes well-trained educators, informed parental involvement, and contextually appropriate play approaches. Recommendations are made to inform future educational practices and policy development.